CODE MIXING USED IN “THE INDAH G SHOW” YOUTUBE CHANNEL BY INDAH GUNAWAN - I Dewa Ayu Dara Agung Laksmi Paramitha; Galuh Febri Putra; Ni Luh Ketut Mas Indrawati (Peneliti.net, 2026)
The phenomenon of code mixing between Indonesian and English on the YouTube channel “The Indah G Show” was the main focus of this study, given the growing popularity of digital media and the trend of bilingualism in Indonesia. The main objective of this analysis was to identify the types of code mixing that dominated Indah Gunawan's utterances as the host in two episodes of her podcast. Understanding this was crucial to seeing how bilingual speakers regulated their language choices in digital interactions. Using qualitative descriptive methods, data were collected through observation and transcription of the host's utterances in the videos “Stoicism & Intellectual Integrity In The Reactionary Age of Social Media Ft. Raditya Dika” and “Indonesia's Academic Dishonesty (‘Joki’), Lack of Merit & Moral Integrity ft. Abigail Limuria (WIUI).” The data were analyzed using Hoffman's theory, which classifies code mixing into Intra Sentential, Intra Lexical, and Involving a change of Pronunciation. The analysis revealed the presence of all three types, with Intra Sentential emerging as the most dominant type. This indicated that Indah G's used of code mixing was a conscious communication strategy, particularly to maintain the flow of spontaneous conversation and discuss certain topics more efficiently.